The influence of COVID-19 pandemic lockdown on the physical performance of professional soccer players: An example of German and Polish leagues - Radziminski, L.; Padrón-Cabo, A.; Konefal, M.; Chmura, P.; Szwarc, A.; Jastrzebski, Z. (International Journal of Environmental Research and Public Health, 2021)
The purpose of this study was to investigate whether the in-season pandemic lockdown influenced physical match performance in professional soccer players who participated in the competition of German Bundesliga and Polish Ekstraklasa. The data from 306 games for German Bundesliga and 296 games for Polish Ekstraklasa were divided into before- and after-lockdown periods. The physical performance of German Bundesliga teams after the 63-day COVID-19 lockdown did not differ significantly from that in the first part of the season. In contrast, Polish Ekstraklasa teams, after the 81-day lockdown, displayed significantly shorter total distances (p < 0.001), shorter high-intensity running distances (p = 0.03), and fewer high-intensity actions (p = 0.02). Moreover, when the effective playing time was considered, teams covered significantly less relative total distance (p < 0.001) and relative high-intensity running distance (p = 0.02). The results of the current study suggest that physical performance during the matches of the German Bundesliga was not influenced by the COVID-19 lockdown, contrary to those of the Polish Ekstraklasa. This difference could have been caused by different break lengths and different restrictions implemented in these countries during the pandemic lockdown.